Increased stable integration efficiency in CHO cells through enhanced nuclear localization of Bxb1 serine integrase - Huhtinen, Olli; Prince, Stuart; Lamminmäki, Urpo; Salbo, Rune; Kulmala, Antti (BioMed Central, 2025)
Background: Mammalian display is an appealing technology for therapeutic antibody development. Despite the advantages of mammalian display, such as full-length IgG display with mammalian glycosylation and its inherent ability to select antibodies with good biophysical properties, the restricted library size and large culture volumes remain challenges. Bxb1 serine integrase is commonly used for the stable genomic integration of antibody genes into mammalian cells, but presently lacks the efficiency required for the display of large mammalian display libraries. To increase the Bxb1 integrase-mediated stable integration efficiency, our study investigates factors that potentially affect the nuclear localization of Bxb1 integrase.
Methods: In an attempt to enhance Bxb1 serine integrase-mediated integration efficiency, we fused various nuclear localization signals (NLS) to the N- and C-termini of the integrase. Concurrently, we co-expressed multiple proteins associated with nuclear transport to assess their impact on the stable integration efficiency of green fluorescent protein (GFP)-encoding DNA and an antibody display cassette into the genome of Chinese hamster ovary (CHO) cells containing a landing pad for Bxb1 integrase-mediated integration.
Results: The nucleoplasmin NLS from Xenopus laevis, when fused to the C-terminus of Bxb1 integrase, demonstrated the highest enhancement in stable integration efficiency among the tested NLS fusions, exhibiting over a 6-fold improvement compared to Bxb1 integrase lacking an NLS fusion. Subsequent additions of extra NLS fusions to the Bxb1 integrase revealed an additional 131% enhancement in stable integration efficiency with the inclusion of two copies of C-terminal nucleoplasmin NLS fusions. Further improvement was achieved by co-expressing the Ran GTPase-activating protein (RanGAP). Finally, to validate the applicability of these findings to more complex proteins, the DNA encoding the membrane-bound clinical antibody abrilumab was stably integrated into the genome of CHO cells using Bxb1 integrase with two copies of C-terminal nucleoplasmin NLS fusions and co-expression of RanGAP. This approach demonstrated over 14-fold increase in integration efficiency compared to Bxb1 integrase lacking an NLS fusion.
Conclusions: This study demonstrates that optimizing the NLS sequence fusion for Bxb1 integrase significantly enhances the stable genomic integration efficiency. These findings provide a practical approach for constructing larger libraries in mammalian cells through the stable integration of genes into a genomic landing pad.